2020
DOI: 10.2142/biophysico.bsj-2020023
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation of human dental pulp stem cells to neuron-like cells by high K<sup>+</sup> stimulation

Abstract: As human-origin cells, human dental pulp stem cells (hDPSCs) are thought to be potentially useful for biological and medical experiments. They are easily obtained from lost primary teeth or extracted wisdom teeth, and they are mesenchymal stem cells that are known to differentiate into osteoblasts, chondrocytes, and adipocytes. Although hDPSCs originate from neural crest cells, it is difficult to induce hDPSCs to differentiate into neuron-like cells. To facilitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In our experiments, βIII-tubulin-positive processes were observed in hDPSCs after seven days in differentiation media, and bipolar type neuron-like cells with elongated neurite-like processes were observed after fourteen days ( Fig 1 ). Whereas differentiated and undifferentiated hDPSCs also expresses a neuronal stem cell marker, nestin, and an astrocyte marker, glial fibrillary acidic protein (GFAP) ( S1 Fig and also reported from other laboratories [ 37 , 50 ]), we have demonstrated that the mRNA expression level of GFAP is much lower than that of βIII-tubulin in undifferentiated and differentiated hDPSC [ 51 ]. Therefore, βIII-tubulin predominates over GFAP in hDPSCs.…”
Section: Discussionsupporting
confidence: 70%
“…In our experiments, βIII-tubulin-positive processes were observed in hDPSCs after seven days in differentiation media, and bipolar type neuron-like cells with elongated neurite-like processes were observed after fourteen days ( Fig 1 ). Whereas differentiated and undifferentiated hDPSCs also expresses a neuronal stem cell marker, nestin, and an astrocyte marker, glial fibrillary acidic protein (GFAP) ( S1 Fig and also reported from other laboratories [ 37 , 50 ]), we have demonstrated that the mRNA expression level of GFAP is much lower than that of βIII-tubulin in undifferentiated and differentiated hDPSC [ 51 ]. Therefore, βIII-tubulin predominates over GFAP in hDPSCs.…”
Section: Discussionsupporting
confidence: 70%
“…The present question is how we can obtain human free nerve endings. One possible answer is the use of human dental pulp stem cells [ 37 , 38 ]. If an in vitro model for a human free nerve ending model in the skin is established, the development of analgesics will advance considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Human epidermal keratinocytes and dermal fibroblasts can be easily obtained as commercially available cells, whereas human neurons are difficult to collect. Oka and Ito have attempted to prepare neurons by differentiating human dental pulp stem cells (hDPSC) [ 66 , 67 ] for this purpose. In particular, Arimura and colleagues compared neurons originating from hDPSCs and rat neurons isolated from the dorsal root ganglion (DRG) [ 67 ].…”
Section: Other Topics For Pain Reliefmentioning
confidence: 99%